Pengaruh Kualitas Layanan dan Komplain Penumpang Terhadap Kinerja Karyawan Maskapai Wings Air Di Bandar Udara Sultan Muhammad Salahuddin Bima - Ainun Sari; Eny Sri Haryati (Lembaga Pengembangan Kinerja Dosen, 2023)
Customer satisfaction is a level of one's feelings after comparing several related factors such as perceived performance or results which can then be compared with the desired expectations. The purpose of this study was to determine the effect of Wings Air airline service quality at Sultan Muhammad Salahuddin Bima Airport, to determine the effect of Wings Air airline passenger complaints at Sultan Muhammad Salahuddin Bima Airport and to determine how much influence service quality and passenger complaints have on employee performance. This research is quantitative research using primary and secondary data. Primary data was obtained from a questionnaire (questionnaire), while secondary data was obtained from PT. Wings Air, articles and website internet. The analysis technique uses descriptive analysis, multiple regression, t-test, and f-test. The results of this study indicate that the calculated F value is 82.002 and a sig value of 0.00 is less than 0.05.